ANALISIS PROTEIN DEFENSIN DARI BIJI JINTEN HITAM (Nigella sativa L.) PADA MENCIT (Mus musculus) YANG DIBERI BIJI JINTEN HITAM MELALUI TEKNIK SDS-PAGE - Rr Bhintarti Suryohastari (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2016)
Abstrak Ns-D1/Ns-D merupakan protein defensin dalam biji jinten hitam (Nigella sativa) dengan berat molekul (BM) 5,4763 kDa/5,4924 kDa. Penelitian ini bertujuan menganalisis defensin dari ekstrak protein biji N. sativa dan mencit (Mus musculus) yang diberi ekstrak protein biji N. sativa. M. musculus dibagi menjadi kelompok K (kontrol) yang tidak diberi ekstrak protein biji N. sativa. Kelompok D1, D2 dan D3 diberi ekstrak protein biji N. sativa dalam dosis rendah (0,35 mg/bb), dosis sedang (0,7 mg/bb) dan dosis tinggi (1,4 mg/bb) selama 7 hari dan pada hari ke-8 dilakukan pengambilan darah. Analisis protein defensin dilakukan melalui teknik SDS-PAGE pada gel poliakrilamid 17% terhadap sampel darah K, D1, D2, D3 dan sampel ekstrak protein biji N. sativa (T). Hasil menunjukkan pada sampel T terdapat pita protein BM 3,4–10 kDa, pada sampel K terdapat pita protein dengan BM 6,1486 kDa dan pada sampel D1, D2 dan D3 terdapat pita protein dengan BM 5,5973 kDa. Munculnya pita protein dengan BM<6 kDa pada D1, D2 dan D3 menunjukkan adanya Ns-D1/Ns-D2 pada M. musculus yang diberikan ekstrak protein biji N. sativa.Abstract Ns-D1/Ns-D2 are defensins protein in the seed of black cumin (Nigella sativa) with molecular masses 5.4763 kDa/5.4924 kDa. This study aimed to analyze the profile of defensin from black cumin seed extract and its presence in blood of mice (Mus musculus) treated with black cumin seed. The mice were divided into 4 groups (K, D1, D2, D3) and each group consisted of 5 mice. K was a group of controlled mice, which was not treated by black cumin seed protein extract, while the D1, D2, and D3 were groups of mice which were treated by black cumin seed protein extract with a low dose (0.35 mg/bw), medium dose (0.7 mg/bw) and high dose (1.4 mg/bw). The treatments were conducted for 7 days. Blood of the treated mice were collected at 8th day. The defensin profiles were analyzed by SDS-PAGE. The results showed that protein bands within 3.4 kDa–10 kDa were found from black cumin seed protein extract (T), at 5.5973 kDa from all treatments and at 6.1486 kDa in control (K1) was detected. The appearance of protein bands lowered than 6 kDa in T, D1, D2 and D3 showed the possibility of the presence of black cumin seed protein extract in the mice blood. Permalink DOI : http://dx.doi.org/10.15408/kauniyah.v9i1.3251